Treating depression at home with transcranial direct current stimulation: a feasibility study - Dragon, Katharina; Abdelnaim, Mohamed A.; Weber, Franziska C.; Heuschert, Markus; Englert, Leon; Langguth, Berthold; Hebel, Tobias; Schecklmann, Martin (Frontiers in Psychiatry, 2024)
Introduction: Treating major depressive disorder (MDD) with transcranial direct current stimulation devices (tDCS) at home has various logistic advantages compared to tDCS treatment in the clinic. However, preliminary (controlled) studies showed side effects such as skin lesions and difficulties in implementation of home-based tDCS. Thus, more data are needed regarding the feasibility and possible disadvantages of home-based tDCS. Methods: 10 outpatients (23 -69 years) with an acute depressive episode were included for this one-arm feasibility study testing home-based tDCS. All patients selfadministered prefrontal tDCS (2mA, 20 minutes, anodal left, cathodal right) at home on 30 consecutive working days supported by video consultations. Correct implementation of the home-based treatment was analyzed with tDCS recordings. Feasibility was examined by treatment compliance. For additional analyses of effectiveness, three depression scores were used: Hamilton depression rating scale (HDRS-21), Major depression inventory (MDI) and the subscale depression of the depression-anxiety-stress scale (DASS). Further, usability was measured with the usability experience questionnaire (UEQ). Tolerability was analyzed by the number of reported adverse events (AEs). Results: Eight patients did not stick to the protocol. AEs were minimal. Four patients responded to the home treatment according to the MDI. Usability was judged positive by the patients. Conclusion: Regular video consultations or other safety concepts are recommended regardless of the number of video sessions actually conducted. Home-based tDCS seems to be safe, effective and handy in our feasibility study warranting further investigation.